(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2011)
The incidence of falls and associated mortality due to falls is a major contributor to injury and leading cause of global burden of disease. Falling is a major cause of personal injury. Builders and Miners represent worker categories representing high rates of fall injuries. In this retrospec tive study, fatal cases of accidental fall were autopsied during the period 01-01-2004 to 31-12- 2009, were analyzed at the Department of Forensic Medicine and Toxicology, J.N. Medical College, Belgaum, Karnataka. The majority of cases were male (70 cases; 89.7%) as com pared with female (8 cases; 10.3%). The male-to-female ratio was 8.7:1. The commonest age group involved was 31-40 years (26 cases; 33.4%), followed by 21-30 years (18 cases; 23.1%). Exercise interventions reduce risk and rate of falls. Research is needed to confirm the contexts in which multi-factorial assessment and intervention, home safety interventions, and other inter ventions are effective.